Levels and sources of volatile organic compounds in homes of children with asthma. (13th January 2014) - Chin, J.‐Y.; Godwin, C.; Parker, E.; Robins, T.; Lewis, T.; Harbin, P.; Batterman, S.
Abstract Many volatile organic compounds (VOCs) are classified as known or possible carcinogens, irritants, and toxicants, and VOC exposure has been associated with the onset and exacerbation of asthma. This study characterizes VOC levels in 126 homes of children with asthma in Detroit, Michigan, USA. The total target VOC concentration ranged from 14 to 2274 μg/m3 (mean = 150 μg/m3; median = 91 μg/m3); 56 VOCs were quantified; and d‐limonene, toluene, p, m‐xylene, and ethyl acetate had the highest concentrations. Based on the potential for adverse health effects, priority VOCs included naphthalene, benzene, 1, 4‐dichlorobenzene, isopropylbenzene, ethylbenzene, styrene, chloroform, 1, 2‐dichloroethane, tetrachloroethene, and trichloroethylene. Concentrations varied mostly due to between‐residence and seasonal variation. Identified emission sources included cigarette smoking, solvent‐related emissions, renovations, household products, and pesticides. The effect of nearby traffic on indoor VOC levels was not distinguished. While concentrations in the Detroit homes were lower than levels found in other North American studies, many homes had elevated VOC levels, including compounds that are known health hazards. Thus, the identification and control of VOC sources are important and prudent, especially for vulnerable individuals. Actions and policies to reduce VOC exposures, for example, sales restrictions, improved product labeling, and consumer education, are recommended.